Assessment of the inter‐rater agreement of corneal cytology and culture findings in canine ulcerative keratitis. (22nd December 2021) - Hamzianpour, N.; Adams, V. J.; Grundon, R. A.; Linn‐Pearl, R.; Scurrell, E.; Rozmanec, M.; Civello, A.; Goss, R.; Watkins, C.; Kearns, H.; Heinrich, C.
Abstract : Objectives: To assess the inter‐rater agreement of corneal cytology findings in canine ulcerative keratitis by veterinary surgeons of different training levels and the agreement of corneal cytology with culture. Materials and Methods: Dogs with progressive ulcerative keratitis were prospectively recruited for corneal cytology and culture. Corneal cytology slides were reviewed by veterinary surgeons of different training levels (three general practitioners, three ophthalmologists and three pathologists). The inter‐rater agreement of cytology findings and agreement of cytology with culture was assessed using the kappa measure of agreement. Results: The study included 145 corneal cytology samples from 143 dogs (145 eyes) with progressive ulcerative keratitis. Positive cultures were obtained from 81 of 145 (56%) eyes. The most commonly isolated pathogens were Streptococcus canis, Pseudomonas aeruginosa and Staphylococcus pseudintermedius . The results demonstrated increased inter‐rater agreement of corneal cytology and increased agreement with culture with increased ocular pathology expertise (pathologists > ophthalmologists > general practitioners). Clinical Significance: This study provides important information about the diagnostic value of corneal cytology in canine ulcerative keratitis and the most common pathogens involved in such cases in the UK. Based on the results of this study, cytology findings should be interpreted in conjunction with the expertise of the observer. For maximal pathogen identification, both cytology and culture should be considered.